The Surveillant Surrounds: Sonar and Sexual Surveillance in Iceland During the Cold War - Johnson, Alix (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2024)
The Sound Surveillance System (SOSUS) was an American naval surveillance network developed over the course of the Cold War. Spanning from the Pacific coast across the Atlantic, SOSUS is remembered for its unprecedented reach and is often figured as a precursor to centralized, networked, and automated surveillance systems today. This article contributes to, and complicates, this history by approaching SOSUS from the perspective of one of its outposts. Iceland was neither an agent nor a target of American surveillance but, as a staging grounds for SOSUS, both shaped and was shaped by this process nevertheless. Theorizing this position as the surveillant surrounds, this article asks after the experience of being interpellated into someone else’s surveillance program, or living where surveillance is a pervasive part of the landscape while occupying neither the position of observer nor observed. In Southern Iceland, I argue, SOSUS both activated and was meaningfully anchored by a local politics of gendered intimacy. Doing so, I shed fresh light on the legacy of SOSUS and make a broader case for attending to the particular place-based dynamics that shape and situate “global” surveillance networks then and today.